Effects of Isoflavones Supplementation on Cholesterol and Fatty Acid Levels of Muscle and Liver Tissues of Quail - Yilmaz, Okkes; Guvenc, Mehmet; Cetintas, Buket; Tuzcu, Mehmet; Dayangac, Alpaslan; Şahin, Kazım (Medwell Online, 2008)
Dietary soy isoflavones reduce hepatic 3-hydroxy-3-methylglutaryl CoA reductase and Delta six desaturase activities and isoflavone metabolites from diet may act as scavengers of reactive oxygen species. Since, dietary intake of soy isoflavones has been associated with reduced lipid perxidation, we investigated the effects of soy isoflavone supplementation on the cholesterol and fatty acid levels of muscle and liver tissue in Japanese quails (Coturnix coturnix japonica). One hundred and twenty quail (5 month old) were assigned to three experimental groups consisting of 10 birds in each group. Birds were fed either a basal diet or a basal diet supplemented with 200 or 800 mg of soy isoflavones/kg of diet. The animals were sacrificed after 10 month and the tissue samples werecollecetd and analyzed in HPLC and GC equipments. Muscle and liver fatty acid composition, palmitic acid (16:0), palmitoleic acid (16: 1, n-9), oleic acid (18: 1, n-9), linoleic (18:2, n-6) and linolenic acids (18:3, n-3) increased (p<0.001), whereas, stearic acid (18:0) (p<0.001) eicosatrienoic (20:3, n-6), arachidonic (20:4, n-6) and eicosapentaenoic acids (20:5, n-3) docosahexaenoic acid level (226, n-3) concentrations decreased with soy isoflavone supplementation. Liver and muscle cholesterol concentrations decreased decreased with soy isoflavone supplementation (p<0.001). As a result, administration of isoflavones was seen to elevate the amount of monounsaturated fatty acids in both muscle and liver tissues, while, reducing the amount of polyunsaturated fatty acids. This suggests that isoflavones influence the liver enzymes taking part in the lipid metabolism.
Keywords: Isoflavone; cholesterol; fatty acid composition; liver; muscle